Pengaruh Literasi Keuangan, Perilaku Keuangan, dan Pengelolaan Arus Kas terhadap Kinerja Keuangan pada UMKM Mie Ayam di Daerah Klaten - May Novita Andriyani; Kristyana Dananti (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
This study is motivated by the low level of financial literacy, financial behavior, and cash flow management among Micro, Small, and Medium Enterprises (MSMEs), which often hinders effective financial management and business sustainability. Chicken noodle MSMEs in the Klaten area represent a sector that requires improved financial management practices to support long-term development. This research aims to analyze the influence of financial literacy, financial behavior, and cash flow management on the financial performance of these MSMEs. The study employs a quantitative method with a survey approach, collecting data through questionnaires distributed to 60 chicken noodle MSME actors using purposive sampling techniques. Data were analyzed using ordinal logistic regression, including stages of descriptive statistics, model fitting information, goodness of fit, pseudo R-square, test of parallel lines, and parameter estimation. The results indicate that financial literacy does not have a significant partial effect on financial performance. In contrast, financial behavior and cash flow management show significant partial effects. However, simultaneously, all three variables significantly influence financial performance. These findings suggest that improving financial literacy, alongside strengthening financial behavior and cash flow management, is essential to enhance the financial performance and sustainability of MSMEs.